2012
DOI: 10.1103/physreve.86.066309
|View full text |Cite
|
Sign up to set email alerts
|

Statistical description of turbulent dispersion

Abstract: We derive a comprehensive statistical model for dispersion of passive or almost passive admixture particles such as fine particulate matter, aerosols, smoke, and fumes in turbulent flow. The model rests on the Markov limit for particle velocity. It is in accordance with the asymptotic structure of turbulence at large Reynolds number as described by Kolmogorov. The model consists of Langevin and diffusion equations in which the damping and diffusivity are expressed by expansions in powers of the reciprocal Kolm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(32 citation statements)
references
References 29 publications
2
29
1
Order By: Relevance
“…2,17 However, the validity of this model has long been uncertain, because it was one of the many possible formulations of the damping function which satisfy the well-mixed criterion. 2,6,9,17 The C −1 0 -expansion brought clarity to this issue, 9 since it showed that the statistics of particle displacement obtained through application of the model according to Eq. (7) is unique up to a relative error of C −2 0 , see Brouwers.…”
Section: -9mentioning
confidence: 99%
See 4 more Smart Citations
“…2,17 However, the validity of this model has long been uncertain, because it was one of the many possible formulations of the damping function which satisfy the well-mixed criterion. 2,6,9,17 The C −1 0 -expansion brought clarity to this issue, 9 since it showed that the statistics of particle displacement obtained through application of the model according to Eq. (7) is unique up to a relative error of C −2 0 , see Brouwers.…”
Section: -9mentioning
confidence: 99%
“…9 The statistical model according to (8) and (9) implies Gaussianity of (d/dt)v i (t). The effects of intermittency apparent in particle accelerations are thus not captured.…”
Section: -9mentioning
confidence: 99%
See 3 more Smart Citations